Salvage nitrous oxide cryotherapy of refractory colon neoplasia embedded within an endoclip - Trindade, Arvind J.; Benias, Petros C.; Cerulli, Maurice A. (Endoscopy International Open, 2018)
Background and study aims This is a case report on use of the CryoBalloon as a salvage technique for ablation of residual neoplasia at an endoscopic mucosal resection site. The site contained an embedded clip that could not be removed at two different sessions by three experienced endoscopists. On follow-up endoscopy, the clips and residual polyp no longer remained. The subtle scar that was present was biopsied and confirmed complete eradication of neoplasia and no polyp tissue. This case shows the potential of the CryoBalloon to ablate unwanted tissue outside of the esophagus.